Social correlates of mental, neurological, and substance use disorders in China and India: a review. (September 2016) - Cheng, Hui G; Shidhaye, Rahul; Charlson, Fiona; Deng, Fei; Lyngdoh, Tanica; Chen, Shengnan; Nanda, Sharmishtha; Lacroix, Kimberly; Baxter, Amanda; Whiteford, Harvey
Summary: Understanding the epidemiological profiles of mental, neurological, and substance use disorders provides opportunities for the identification of high-risk population subgroups and for the development of effective country-specific prevention and intervention strategies. Guided by the Conceptual Framework for Action on the Social Determinants of Health by WHO we reviewed the literature to examine the association between a range of social correlates (eg, sex, age, education, income, urbanicity, marital status, and regional differences) and mental, neurological, and substance use disorders in China and India, the most populous countries in the world. We looked for papers on mental, neurological, and substance use disorders with location identifiers and socioeconomic correlates published between 1990 and 2015 and our search found 65 relevant studies from China and 29 from India. Several association patterns between social correlates and mental, neurological, and substance use disorders were not consistent with those reported in high-income countries, including a high concentration of middle-aged men with alcohol use disorders in China and to a lesser extent in India, and a positive association between being married and depression among women in India. Consistent with previous global reports, low education and poverty were associated with higher occurrence of dementia in both China and India, although there is evidence of an interaction between education and income in the risk for dementia in China. Large variations across regions and ethnic groups were consistently documented in China. These unique correlation patterns for mental, neurological, and substance use disorders identified in China and India emphasise the importance of understanding the local social context when planning targeted strategies to reduce the burden of these disorders. High-quality, up-to-date information about the constantly changing pattern of societal factors correlated with mental, neurological, and substance use disorders is urgently needed to help reduce the large and increasing negative social and economic effects that these conditions are having in China, India, and other low-income and middle-income countries.